Innovative Ideas for School Business Officials: Best Practices from ASBO's Pinnacle Awards - Ritchey, David A. (Rowman & Littlefield Publishers, 2003)
School business officials are known for their innovative, meaningful contributions to the improvement of their profession and the efficiency of school entities. The ASBO International Pinnacle Awards were established to recognize outstanding practices and new ideas that result in significant contributions to school entities. Successful applications have focused on areas such as budgeting, construction, cost savings, energy conservation, resource reallocation, safety, transportation, and technology. The profiles of Pinnacle Award applications in Innovative Ideas for School Business Officials are intended to provide school business officials with specific ideas to save money or improve processes in a variety of areas related to the day-to-day operation of schools. The money and time saved by implementing these ideas can then be applied where needed most, whether for classroom instruction, additional teacher preparation, other human resources needs to guarantee all students are taught by highly qualified professionals, to balance budgets in maintenance or other areas, or to replenish a rainy day fund. As one of the applicants said, utilizing ideas here may help school business officials to do "what is best for the children."